Clinical assessment of various imaging systems for dental plaque scoring after the use of 3 different toothpastes - MEŞELİ, SİMGE; KORKUT, BORA; AKSU, MEHMET BURAK; TAĞTEKİN, DİLEK (My University, 2023)
Purpose: This study was conducted to compare dental plaque scores obtained through clinical examinations and various imaging techniques, as well as to assess the effectiveness of herbal and conventional toothpastes for plaque removal. Materials and Methods: Thirty volunteers were divided into 3 groups. Each group was given a different toothpaste (from 2 herbal toothpastes and a conventional toothpaste) with which to brush their teeth for 21 days. Both initially and after brushing, dental plaque samples were collected, and plaque on the buccal surfaces of anterior teeth was scored using several imaging systems after staining with a disclosing agent. Specifically, digital dental photography, intraoral digital scanning, and FluoreCam imaging were employed to capture intraoral images. The Turesky Modified QuigleyHein Plaque Index was used for clinical examination and image analysis. Quantitative polymerase chain reaction analyses and correlational assessments between clinical examination and imaging scores were conducted before and after toothpaste use. The Shapiro-Wilk test and Pearson correlations were utilized. Results: The lowest mean value was observed in the clinical examination without staining, while the highest was obtained using the FluoreCam method. No significant change was found in the level of any microorganism assessed following toothpaste use (P<0.05), with the exception of a decrease in S. mutans levels after using conventional toothpaste (P<0.05). Conclusion: Herbal toothpaste demonstrated plaque-removal effectiveness comparable to that of conventional toothpaste. The use of imaging methods for measuring plaque index has been suggested as a means to educate patients about plaque control and promote ongoing oral care.(Imaging Sci Dent 20220208)
Keywords: Dental Plaque; Photography; Dental; Imaging; Three-Dimensional; Fluorescence